A THE ISSUE OF INNOVATIVE APPROACH TO TEACHING ENGLISH: THE ISSUE OF INNOVATIVE APPROACH TO TEACHING ENGLISH - Muradov, Utkir (Журнал иностранных языков и лингвистики, 2022)
The article discusses ways to use innovative methods in the teaching process based on foreign experience in English lessons in order to modernize the organization of the educational process.